Atmospheric effects on measurements of distance to Earth artificial satellites - Kablak, N.; Klimyk, V.; Shvalagin, I.; Kablak, U. (Кинематика и физика небесных тел, 2005)
This paper is devoted to the problem of accuracy increasing in allowing for Earth’s atmosphere influences on results of daily ranging observations of the Earth artificial satellites (ASE). Atmosphere delays and their spatial-timely variations for spherical-symmetrical and nonspherical models of atmosphere were determined radiosounding data gathered during a year in Ukraine region using, developed valuing and analysis of models reductions to over of atmosphere, which recommended of IERS for processing distance-ranging observations of the Earth artificial satellites. Investigated and improved models of reductions to over of the atmosphere on the basis of discovered regional and local peculiarity’s of influence atmosphere on the laser and radio ranging observations of the Earth artificial satellites.